The Effect of Taste, Location, and Quality of Service on Customer Satisfaction in Mutia Garden Medan Restaurant - Feriani Astuti Tarigan; Krismon Wijaya (Institute of Computer Science (IOCS), 2022)
This research was conducted with the aim to find out how the influence given by taste, location atmosphere and service quality on customer satisfaction at Mutia Garden Restaurant Medan. The implementation of the research used a questionnaire as an instrument in the study. The data analysis method used in the study consisted of multiple linear regression analysis, coefficient of determination or R2, partial testing and also simultaneous testing. The results of this study indicate that partially or simultaneously the variables of taste, location atmosphere, and service quality have a significant influence on customer satisfaction at Mutia Garden Medan restaurant.